Literature Review : Pengaruh Gizi dan Kesehatan terhadap Pertumbuhan dan Perkembangan pada Anak - Melianti, EKA Otaviani; Yuliana, Yuliana; Yulastri, Asmar (JGK: Jurnal Gizi dan Kesehatan, 2023)
Children are the future of the nation and state because they are the next generation. So that children can grow and develop normally, the role of nutrition is very vital and must be considered. With the fulfillment of nutritional needs, such as carbohydrates as a source of energy (energy), protein as a builder substance and vitamins/minerals as a regulatory substance. will help prevent disease. This results in stunted growth and development of children. Growth and development will be assisted by the proper nutritional composition; healthy food is food that is adjusted to the activity level and age of consumers. This is so that by fulfilling nutritional needs, the components of maintenance, growth, repair of damaged/worn/lost bodies, and reproduction of physical energy can be carried out entirely. Objektif: The benefits of balanced nutrition in children can make their body, intelligence, and abilities develop properly. rapidly. Physically, with good nutrition, children will be healthier and not get sick easily. Methods: The method used is the study of literature from various international and national journals, with a descriptive analysis approach. Results: The results showed that there was a positive relationship with strong strength and statistically significant between growth stimulation and child development. Conclusion: Nutrition is an important factor in the process of physical growth and development of children who are growing and developing. The nutrients needed include breast milk (ASI), energy, prolein, fat, carbohydrates/carbohydrates, vitamins and minerals. In providing nutrients, it is hoped that it will be in accordance with a balanced menu and large portions adjusted to the child's acceptability